Determinants of loans growth in cooperative banks in Poland: Does capital ratio matter? - Kowalska, Iwona; Olszak, Małgorzata; Świtała, Filip (Determinanty stopy wzrostu kredytów banków spółdzielczych w Polsce: Czy współczynnik kapitałowy ma znaczenie?, 2019)
This article examines the impact of bank capital ratios on cooperative banks’ lending by comparing differences in loan growth to differences in capital ratios at sets of banks that are clustered based on capital ratio size. Applying a fixed-effects estimator to a sample of cooperative banks operating in Poland and using a unique quarterly dataset covering the period of 2000:1-2012:4, we find that loans’ growth is particularly capitalconstrained in poorly-capitalized banks, but only in non-recessionary ones. Lending of poorly capitalized banks is strongly affected by the interest rate margin, which is also important in determining the loans’ growth of medium and large cooperative banks. Generally the results add support to the view that small banks, such as cooperative banks, are not capital-constrained in recessionary periods, thus their customers do not suffer from the capital crunch in unfavourable macroeconomic conditions. However, their lending activity is procyclical, because increases in the unemployment rate result in decreases in the loans’ growth of cooperative banks in Poland
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 49-64
Keywords: lending activity; capital adequacy ratio; procyclicality; cooperative banks; aktywność kredytowa; współczynnik adekwatności kapitałowej; procykliczność; banki spółdzielcze